Rāḥat al-arwāḥ wa-muʾnis al-ashbāḥ : Dar sharḥ-i zindagānī, faḍāyil u muʿjizāt-i aʾimma-yi aṭhār - Sabzawārī, Ḥasan Shīʿī, (Miras Maktoob, ISBN: 9789004365452., 2019)
In Islam, Twelver-Shīʿism is based on the claim that the rightful successors to the Prophet were his son-in-law ʿAlī b. Abī Ṭālib (d. 40/661) and eleven of his descendants through his marriage with Fāṭima, ending with the grand occultation of the twelfth and last imam, Muḥammad al-Mahdī in 329/940. In the centuries following the occultation of the last imam, there emerged a special type of hagiographic literature glorifying the lives and wonders of the Prophet, his daughter Fāṭima, and the twelve infallible imams. The importance of these works was not just informative and apologetic; they also had a didactic side insofar as the imams were regarded as a channel for God's grace to man, it being through them that man could learn how to fulfil God's wish of obeying Him. Composed around 755/1355 for the Sarbadār ruler of Sabzawār by Ḥasan Shīʿī Sabzawārī, this elegantly written Persian volume is a fine specimen of this particular type of writings.